2016
DOI: 10.1016/j.nimb.2015.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous dispersion and band gap reduction in UO2+ and its possible coupling to the coherent polaronic quantum state

Abstract: Hypervalent UO 2 , UO 2(+x) formed by both addition of excess O and photoexcitation, exhibits a number of unusual or often unique properties that point to it hosting a polaronic Bose-Einstein(-Mott) condensate. A more thorough analysis of the O x-ray absorption spectra of UO 2 , U 4 O 9 , and U 3 O 7 shows that the anomalous increase in the width of the spectra features assigned to predominantly U 5f and 6d final states that points to increased dispersion of these bands occurs on the low energy side correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Importantly, according to the fingerprint peaks (U–O 5 VV), the band gaps of UN 1.66 , UO 2 , and UN x O y were estimated to be 0.65, 1.8, and 1.4 eV, respectively. The band gap of UO 2 determined in this method is a little smaller from 2.1 eV obtained in the optical spectrum and 1.5 eV obtained by X-ray absorption spectra . Moreover, the thermal stability of uranium nitride and oxynitride film in an ultrahigh vacuum environment using Auger electron spectroscopy (AES) revealed that UN 1.42 O 0.23 film exhibited better thermal stability than UN 1.66 film below 573 K .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Importantly, according to the fingerprint peaks (U–O 5 VV), the band gaps of UN 1.66 , UO 2 , and UN x O y were estimated to be 0.65, 1.8, and 1.4 eV, respectively. The band gap of UO 2 determined in this method is a little smaller from 2.1 eV obtained in the optical spectrum and 1.5 eV obtained by X-ray absorption spectra . Moreover, the thermal stability of uranium nitride and oxynitride film in an ultrahigh vacuum environment using Auger electron spectroscopy (AES) revealed that UN 1.42 O 0.23 film exhibited better thermal stability than UN 1.66 film below 573 K .…”
Section: Introductionmentioning
confidence: 77%
“…The band gap of UO 2 determined in this method is a little smaller from 2.1 eV obtained in the optical spectrum 6 and 1.5 eV obtained by X-ray absorption spectra. 7 Moreover, the thermal stability of uranium nitride and oxynitride film in an ultrahigh vacuum environment using Auger electron spectroscopy (AES) revealed that UN 1.42 O 0.23 film exhibited better thermal stability than UN 1.66 film below 573 K. 8 Interestingly, when the temperature exceeded 573 K, O in UN 1.66 and UN 1.42 O 0.23 films decreased significantly, whereas N increased due to the diffusion of N from the inner to outer layer. These findings suggest a diversified chemical formula of UN x O y , as evidenced by electron-energy-loss spectroscopy 9 and first-principles calculations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 Uranium oxides show exciting interdependence between their physicochemical properties and complex electronic structures. 10,11 In particular, the presence of delocalized valence electrons can be seen to stimulate oxidation of UO 2 . Accommodation of excess oxygen atoms onto specific sites in the fluorite (Fm3̅ m) lattice has the potential to increase hybridization between O 2p and U 5f/6d orbitals.…”
mentioning
confidence: 99%
“…As previously reported, the spectral features strongly depend on the preparation method. [26] In case of the UO 2 powder, the signals corresponding to the hybridized uranium 5f 3 states were more pronounced than in the dispersed sample. In Figure 6 and the reference spectrum by Jollet et al, the 5f 3 states appear as "shoulders" towards lower energies of the 5f 2 6de g 1 signal, whereas in the UO 2 powder both signals are distinguishable and exhibit comparable intensities ( Figure 7).…”
Section: (Jcpds [36-0089])mentioning
confidence: 90%